Social Work and Elder Abuse: A Foucauldian Analysis - Jason L. Powell (Social Work & Society, 2012)
Recently, there an accelerating interest in elder abuse has arisen due to the implementation of community care policies relying upon informal care and a relentless political campaign to legitimise an enforced obligation to care. The use of care management technologies that focus on assessment and inspection, can, in this policy climate, become a means of surveillance and enforcement of informal caring. It is argued that Michel Foucault offers a set of strategies (Foucault 1977: 205) for understanding how the discourses on community care construct older people's experiences and their identities, as constructed subjects and objects of managerial knowledge.